This is how i do it! proportionality and invention in a mathematics class - De Oliveira, Marta Elaine; Clareto, Sônia Maria [UNESP] (FapUNIFESP (SciELO), 2020)
This article presents itself as a writing essay in a mathematics classroom by means of fabulations. The fabulations and questions that take shape here were produced in a doctoral research. A fabulation as a way of writing that provokes thought and learning as an affirmation of life. The notion of fable, treated in this text, is thought together with Deleuze and constitutes a movement of problematization and resistance in Mathematics education. A displacement in the playback mode of a model that arises as a path that leads to the correct result and adequate thought, brings the invention of a way ofoperating that troubles a thought and breaks a way already regulated. Faced with this, a problematization aligned with this fiction-curriculum-school-history-classroom-of-mathematics: At the service of what kind of life is knowledge placed?.
É assim que eu faço! Proporcionalidade e Invenção em uma Aula de Matemática
Keywords: Fabulação; Classroom; Theorem of Tales